Ultrafast dynamics and evolution of ion-induced opacity in transparent dielectrics. (12th October 2020) - Coughlan, M; Donnelly, H; Breslin, N; Arthur, C; Nersisyan, G; Yeung, M; Villagomez-Bernabe, B; Afshari, M; Currell, F; Zepf, M; Dromey, B
Abstract: Recently, measurements of few-picosecond (ps, 10 −12 s) pulses of laser-driven protons were realised by the observation of transient opacity in SiO2 . This ultrafast response could be understood by the formation of self-trapped excitonic states in the material, creating a rapid de-excitation channel for conduction band electrons. Here we extend this work to examine the onset and evolution of an ion-induced opacity in transparent dielectrics, namely multicomponent variants of SiO2 . The fast recovery observed in SiO2 is in sharp contrast to borosilicate (BK7) and soda-lime glasses. We find that the opacity decay timescales for BK7 and soda-lime glass are orders of magnitude greater than the 3.5 ps proton pump pulse duration and discuss the underlying processes which may be affecting the extended recovery of the material. Simultaneous probing with 2nd harmonic radiation allows estimates of ultrafast electron dynamics due to proton interactions in matter to be investigated, this indicates that a rapid evolution of an initially unstructured ion-induced dose distribution seeds the longer term recovery pathways in the irradiated dielectrics. When combined, these results demonstrate the efficacy of utilising ultrafast laser-driven ionising radiation along with highly synchronised probe pulses to enable the study of ion-induced damage in matter on ultrafast timescales in real time.